Cavernous Breast Hemangioma Mimicking an Invasive Lesion on Contrast-Enhanced MRI - Menelaos Zafrakas; Panayiota Papasozomenou; Panayiotis Eskitzis; Demetrios Zouzoulas; Glyceria Boulogianni; Thomas Zaramboukas (Case Reports in Surgery)
Hemangiomas are vascular lesions, which are only rarely located in the breast. Larger breast hemangiomas may be detected by clinical examination, mammography, and breast ultrasound, whereas smaller lesions are usually incidental findings. We present a rare case of a 43-year-old woman with a cavernous hemangioma of the breast, presenting only on MRI and evading mammographic and ultrasonographic imaging. On breast MRI, a small lesion with irregular margins was detected in the right breast, and following gadolinium contrast medium administration, a type 3 curve, with rapid initial rise, followed by reduction in enhancement (washout) in the delayed phase was noted, raising suspicion for malignancy. The lesion could not be visualized on second-look targeted breast ultrasound and full-field digital mammography. A wide local excision was performed after 3 T MRI-guided hook wire localization and diagnosis of cavernous hemangioma was established histologically. Cavernous hemangioma is a rare breast lesion, with only few cases reported in the literature, and this is the first case with a presentation mimicking an invasive tumor on contrast-enhanced MRI.